Gut Hormones as Potential Therapeutic Targets or Biomarkers of Response in Depression: The Case of Motilin - Rajkumar, Ravi Philip (Life (Basel, Switzerland), 2021)
Recent research has identified the gut–brain axis as a key mechanistic pathway and potential therapeutic target in depression. In this paper, the potential role of gut hormones as potential treatments or predictors of response in depression is examined, with specific reference to the peptide hormone motilin. This possibility is explored through two methods: (1) a conceptual review of the possible links between motilin and depression, including evidence from animal and human research as well as clinical trials, based on a literature search of three scientific databases, and (2) an analysis of the relationship between a functional polymorphism (rs2281820) of the motilin (MLN) gene and cross-national variations in the prevalence of depression based on allele frequency data after correction for potential confounders. It was observed that (1) there are several plausible mechanisms, including interactions with diet, monoamine, and neuroendocrine pathways, to suggest that motilin may be relevant to the pathophysiology and treatment of depression, and (2) there was a significant correlation between rs2281820 allele frequencies and the prevalence of depression after correcting for multiple confounding factors. These results suggest that further evaluation of the utility of motilin and related gut peptides as markers of antidepressant response is required and that these molecular pathways represent potential future mechanisms for antidepressant drug development.